Juridical Study of Telemedicine Consulting Services in Indonesia - Eman Sulaiman; Trini Handayani; Aji Mulyana (SOEPRA, 2021)
Abstract: Technology has an important role in human life. The rapid advancement of telecommunications technology has influenced the world of medicine. One of them is the use of telemedicine in health consultations between doctors and patients. Telemedicine is a long-distance health service by health professionals using information and communication technology. Telemedicine can provide various conveniences in conducting health consultations. However, problems arise related to the implementation of this telemedicine, including problems related to the legal aspects of telemedicine. The purpose of this study was to determine the legal aspects of telemedicine in Indonesia and the liability of doctors in the event of adverse effects resulting from treatment through telemedicine consultation. The research method in this paper is normative juridical. This article describes various problems related to the implementation of telemedicine as well as legal aspects related to telemedicine services in Indonesia. Based on observations, there are no unequivocal legal regulations regarding the implementation of telemedicine in Indonesia, such as the legality of practice permits, legality of practice sites, medical records, data accuracy, medical approval, confidentiality and security of patient data. So that effort are needed from the government through the Ministry of Health to pay more attention to telemedicine problems and make clear and firm legal rules to frame the implementation of telemedicine in Indonesia. Abstrak: Teknologi memiliki peranan yang penting bagi kehidupan manusia. Kemajuan teknologi telekomunikasi yang pesat telah mempengaruhi dunia kedokteran. Salah satunya adalah penggunaan telemedisin dalam konsultasi kesehatan antara dokter dengan pasien. Telemedisin merupakan suatu pelayanan kesehatan jarak jauh oleh oleh profesional kesehatan dengan menggunakan teknologi informasi dan komunikasi. Telemedisin dapat memberikan berbagai kemudahan dalam melakukan konsultasi kesehatan. Namun muncul permasalahan terkait dengan pelaksanaan telemedisin ini, diantaranya adalah masalah yang berkaitan dengan aspek hukum telemedisin. Tujuan dari penelitian ini adalah untuk mengetahui aspek hukum telemedisin di Indonesia dan pertanggungjawaban dokter apabila terjadi adverse effect yang merupakan hasil dari tatalaksana melalui konsultasi telemedisin. Metode penelitian tulisan ini adalah yuridis normatif. Artikel ini menjelaskan berbagai permasalahan berkaitan dengan implementasi telemedisin serta aspek hukum yang berkaitan dengan layanan telemedisin di Indonesia. Berdasarkan hasil pengamatan, belum ada aturan hukum yang secara jelas dan tegas terkait pelaksanaan telemedisin di Indonesia, seperti legalitas izin praktik, legalitas tempat praktik, rekam medik, keakuratan data, persetujuan medis, kerahasiaan dan keamanan data pasien. Sehingga diperlukan upaya dari pemerintah melalui Kementerian Kesehatan untuk lebih memberikan perhatian pada permasalahan telemedisin serta membuat aturan hukum yang jelas dan tegas untuk membingkai pelaksanaannya telemedisin di Indonesia.